Alternative and Low‐Use‐Rate Herbicides Offer Similar Levels of Weed Control to Current Standards in Turfgrass Lawns in the Upper Midwest. Issue 1 (1st October 2019) - Hockemeyer, K.; Koch, P.L.
Abstract : Core Ideas: Demand exists for effective selective herbicides that do not contain the active ingredient 2, 4‐D. Multiple low‐use‐rate and biological‐based herbicides provided effective weed control. The 2, 4‐D‐containing three‐way Trimec 1000 consistently reduced weed populations more effectively than alternatives though alternative options exist for those customers concerned with the non‐target impacts of 2, 4‐D. Weed control in turfgrass lawns is often reliant on herbicides containing the active ingredient 2, 4‐dichlorophenoxyacetic acid (2, 4‐D). Concerns over the widespread use of 2, 4‐D‐based herbicides has led to the development of alternative herbicides with low use rates or classifications such as reduced risk or organic. The objective of this study was to test alternative herbicide products in the field and compare their efficacy to a standard three‐way mixture containing 2, 4‐D, dicamba, and mecoprop. Nine different herbicides were tested for their efficacy over a 3‐year period on a turfgrass lawn in Madison, WI. All treatments reduced weed cover compared with the non‐treated control. The three‐way standard herbicide Trimec 1000 consistently reduced weed populations most effectively. Low‐use‐rate products like Defendor and Turflon Ester Ultra and the mineral oil‐based adjuvant Civitas WEEDfree all reduced weed populations to levels comparable to that of Trimec 1000. These results indicate that a small number of non‐2, 4‐D options are available for effective weed control on cool‐season turfgrasses in the upper Midwest.